Perbedaan Efektivitas Kuliah Metode Daring dan Metode Luring Pada Mata Kuliah Klasifikasi dan Kodefikasi Penyakit - Shafa Aulia Ananda Hermanto; Puteri Fannya; Dina Sonia; Noor Yulia (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Online/distance learning is learning that is carried out without face-to-face meetings, or using assistive platforms. Offline or face-to-face learning is a learning system that does not use an internet connection or use a learning assistant platform, in other words students and lecturers meet face to face. This study aims to find out the differences and effectiveness of learning online and offline methods in disease classification and coding courses conducted by Medical Record Students at Esa Unggul University. This study uses a quantitative approach to the research method, namely inferential analysis using the t dependent test instrument. The effectiveness of online learning methods is 33 or 44.0%, and the effectiveness of offline learning methods is 40 or 53.3%. based on the results of the dependent t-test, a significant score of 0.000 was obtained between the effectiveness of online learning and the effectiveness of offline learning. So it can be concluded that there are differences between online learning methods and offline learning methods. So it is advisable to combine learning methods or use hybrid learning methods.